Comparison of once daily atenolol, nitrendipine and their combination in mild to moderate essential hypertension. - Maclean, D (1990)
1. The aim of the study was to compare the efficacy and the tolerability of treatment with atenolol (50-100 mg once daily), nitrendipine (20-40 mg once daily) and their combination (atenolol 50 mg + nitrendipine 20 mg) once daily in patients with mild to moderate essential hypertension. 2. The study was a randomised, double-blind, placebo controlled parallel groups design: blood pressures were measured at 'trough' effect (i.e. 24 h after dosing) to assess the adequacy of once-daily treatment. 3. Mean blood pressures (mm Hg) recorded on four occasions over 12 weeks of treatment were significantly lower both with atenolol (155/97 sitting: 155/104 standing) and with the combination of atenolol plus nitrendipine (153/96 sitting: 152/104 standing) than with placebo (169/108 sitting: 169/114 standing). Nitrendipine alone had no significant effect on blood pressure 24 h after dosing (165/104 sitting: 165/110 standing). 4. Withdrawals due to adverse effects were more common during treatment with nitrendipine: 7/32 of the patients experienced adverse effects attributable to intense systemic vasodilatation (e.g., flushing, erythema, headache). 2/37 patients taking atenolol were withdrawn: one because he developed a psoriatic rash and the other because of impaired peripheral circulation. Of the 35 patients taking combination treatment, two were withdrawn: one developed headaches and dyspnoea, and the other asthma. 5. The results suggest that once daily dosing with nitrendipine does not control blood pressure throughout the 24 h period in the majority of patients, and is associated with a considerable burden of adverse effects. Combination treatment was better tolerated but appeared to offer no advantages over atenolol alone in terms either of blood pressure control or adverse effects.